Knowledge sharing model for performance improvement of outsourced facilities management in government buildings / Lilis Shereena Safiee ... [et al.] - Safiee, Lilis Shereena; Mohammad Ali, Irwan; Mohd Radzuan, Nor Amin; Hasim, Mohamad Sufian (2024)
Outsourcing FM services was introduced in Malaysia in 1996 to lessen the government's burden. By transferring the resource management of non-core activities such as housekeeping, service equipment maintenance, and security services, the government can focus on increasing public service delivery. Government buildings and facilities represent a significant financial investment of public money; thus, a more strategic and effective approach is needed through knowledge-sharing activities. Among the problems resulting from outsourced FM are a lack of communication, weak performance management, and poor service delivery. The objectives of the study are to identify the determinant factors of knowledge sharing (KS) for the performance improvement of outsourced FM in government buildings and examine the relationship between KS determinant factors and the performance improvement of outsourced FM in government buildings. The research employed a quantitative approach, where a set of questionnaires was developed based on prior findings on KS and the Theory of Planned Behavior (TPB). 112 outsourced FM personnel participated in the self-administered online survey. Analysis was done in two stages, using exploratory factor analysis through SPSS version 28 and structural equation modelling (SEM) through Smart PLS 4.0. The results confirm five group factors: self-attitude (SA), nature of knowledge (NK), motivation to share (MS), organisational culture (OC), and opportunity to share (OS). From the hypothesis testing, the finding discloses only individual dimensions; SA and NK have a significant impact on improving the performance of outsourced FM in government buildings. buildings.